Karakteristik Batuan Tuff Pada Daerah Mootilango Kabupaten Gorontalo Utara Provinsi Gorontalo - Muh Hasym As'ari; Ahmad Zainuri; Muhammad Kasim (Universitas Negeri Gorontalo, 2025)
The study area is located in Mootilango Village Anggrek Sub-district, North Gorontalo Regency, Gorontalo Province. Geographically, the study area is located at coordinates 0° 46' 0